Sleep disorders in Wilson's disease - Nevsimalova, S; Buskova, J; Bruha, R; Kemlink, D; Sonka, K; Vitek, L; Marecek, Z (European journal of neurology, 2011)
BACKGROUND: Wilson's disease (WD) is an autosomal recessive inherited disease with copper accumulation; neurodegeneration is associated with dopaminergic deficit. The aim of the study is to verify sleep co-morbidity by questionnaire and objective sleep examinations (polysomnography, multiple sleep latency test). METHODS: fifty-five patients with WD (22 hepatic, 28 neurological, five asymptomatic form) and 55 age- and sex-matched control subjects completed a questionnaire concerning their sleep habits, sleep co-morbidity, Epworth sleepiness scale (ESS), and answered screening questions for rapid eye movement (REM) behaviour disorder (RBD-SQ). Twenty-four patients with WD and control subjects underwent polysomnographic examination. RESULTS: unlike the controls, patients with WD were more prone to daytime napping accompanied by tiredness and excessive daytime sleepiness, cataplexy-like episodes and poor nocturnal sleep. Their mean ESS as well as RBD-SQ was higher than that of the controls. Total sleep time was lower, accompanied by decreased sleep efficiency and increased wakefulness. Patients with WD had lower latency of stage 1 and stage 2 of non-rapid eye movement (NREM) sleep and less amount of NREM sleep stage 2. One-third of the patients with WD were found to have short or borderline multiple sleep latency test (MSLT) values independent of nocturnal pathology (sleep apnoea, periodic leg movements and/or restless leg syndrome). CONCLUSIONS: patients with WD often suffer from sleep disturbances (regardless of the clinical form). The spectrum of sleep/wake symptoms raises the suspicion that altered REM sleep function may also be involved.
Keywords: Sleep Wake Disorders; Polysomnography; Surveys and Questionnaires; Adult; Male; lidé; dospělí; hepatolentikulární degenerace; ženské pohlaví; mužské pohlaví; lidé středního věku; polysomnografie; Female; Middle Aged; Hepatolenticular Degeneration; Humans; průzkumy a dotazníky; poruchy spánku a bdění